Application intentions among crowd workers: a case study/ Zuria Akmal Saad ... [et al.] - Akmal Saad, Zuria; Fauzi, Muhammad Ashraf; Osman, Azim Azuan; Ramli, Mohd Safwan (Universiti Teknologi MARA, Sabah, 2024)
This study aims to understand the job application intentions of crowd workers utilising an online crowdsourcing platform from the perspective of Signalling Theory. The study involved 66 students enrolled in the Bachelor of Office System Management program at Universiti Teknologi MARA, Pahang, who participated as parttime crowd workers on various online crowdsourcing platforms to fulfil the study's requirements. Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed to examine the relationships between the variables within the proposed model. The study's findings revealed positive and significant relationships between job characteristics and person-job fit as the signal to the crowd worker to be attracted to the job in the online crowdsourcing platform. Thus, job attractiveness failed to navigate the job application intention as the platform involvement is to generate income. The study contributed to understanding the deeper involvement of crowd workers through signal channels by the online crowdsourcing platform, particularly from the new entrants. The right channel portrayed will increase the effectiveness of the online crowdsourcing environment and indirectly satisfy all parties involved.